1985
DOI: 10.2307/1938007
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Minnows, Piscivorous Bass, and Stream Algae: Dynamics of a Strong Interaction

Abstract: Striking differences in pool—to—pool distributions of an algae—grazing minnow (Campostoma anomalum), attached algae (predominantly Spirogyra sp. and Rhizoclonium sp.), and bass (Micropterus salmoides and M. punctulatus) are known to occur in some small Oklahoma streams. This study evaluates the complementarity of bass, Campostoma, and algae at different seasons, and uses in—stream experimental manipulations of bass and Campostoma to determine if the patterns resulted from strong interactions between predators,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
472
3
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 598 publications
(497 citation statements)
references
References 33 publications
21
472
3
1
Order By: Relevance
“…These results differ to those for several other species in which the introduction of shelter had little or no effect on spatial distribution in the absence of predators (Werner et al, 1983a;Utne et al, 1993). However, there are many examples showing that in the presence of predators, aquatic fauna shift to areas offering improved shelter from predation (Stein, 1977;Stein and Magnuson, 1976;Sih, 1982;Vuorinen et al, 1983;Power et al, 1985;Utne et al, 1993). Thus, in terms of the hypothesis of predation risk, decreased risk of predation appears to be an important factor underpinning the preferred use of mangrove habitats by juvenile fish.…”
Section: Predation Pressure and Use Of Sheltercontrasting
confidence: 60%
“…These results differ to those for several other species in which the introduction of shelter had little or no effect on spatial distribution in the absence of predators (Werner et al, 1983a;Utne et al, 1993). However, there are many examples showing that in the presence of predators, aquatic fauna shift to areas offering improved shelter from predation (Stein, 1977;Stein and Magnuson, 1976;Sih, 1982;Vuorinen et al, 1983;Power et al, 1985;Utne et al, 1993). Thus, in terms of the hypothesis of predation risk, decreased risk of predation appears to be an important factor underpinning the preferred use of mangrove habitats by juvenile fish.…”
Section: Predation Pressure and Use Of Sheltercontrasting
confidence: 60%
“…These observations could be the result of a trait-mediated cascade whereby native whelks hide rather than forage in the presence of crabs or relocate higher intertidally to avoid crabs and to consume barnacles instead of oysters. Similar reductions in foraging activity and behavioral shifts in habitat use are commonly displayed by prey in other systems (Gastreich 1999;Power et al 1985). In contrast, our survey and experimental results (Figs.…”
Section: Discussionmentioning
confidence: 55%
“…Smaller grazing minnows (when motivated by predator additions) could traverse these riffles. We found that emigration, rather than predation, accounted for about 50% of the reduction in minnow numbers following bass addition to a Campostoma pool (Power et al, 1985). This clear flowing river with its replicated pool habitats facilitated experiments that supported predictions from the trophic cascade model (Estes and Palmisano, 1974;Estes et al, 1978) and theory predicting the stabilizing effects of the differential mobility of predators versus prey through patchy environments (Huffaker, 1958;Hastings, 1977).…”
Section: When Is a Pool A Pool?mentioning
confidence: 54%
“…Each of these habitats partially delimit arenas for ecologically important interactions. The rough replication of habitat units (e.g., pools along channel reaches) can be useful for comparisons and manipulations (e.g., Power, 1984a;Power and Matthews, 1983;Power et al, 1985). Over time, discharge fluctuations of sufficient magnitude (e.g., bed scouring floods or dewatering) periodically remove organisms and reset river food webs, offering repeated opportunities to study food web assembly.…”
Section: Introductionmentioning
confidence: 99%